Structure and anticoagulant activity of sulfated fucans. Comparison between the regular, repetitive, and linear fucans from echinoderms with the more heterogeneous and branched polymers from brown algae - Pereira, M.S. (Universidade Federal do Rio de Janeiro, Brazil.); Mulloy, B; Mourao, P.A.S (The Journal of biological chemistry, 1999)
Sulfated fucans are among the most widely studied of all the sulfated polysaccharides of non-mammalian origin that exhibit biological activities in mammalian systems. Examples of these polysaccharides extracted from echinoderms have simple structures, composed of oligosaccharide repeating units within which the residues differ by specific patterns of sulfation among different species. In contrast the algal fucans may have some regular repeating structure but are clearly more heterogeneous when compared with the echinoderm fucans. The structures of the sulfated fucans from brown algae also vary from species to species. We compared the anticoagulant activity of the regular and repetitive fucans from echinoderms with that of the more heterogeneous fucans from three species of brown algae. Our results indicate that different structural features determine not only the anticoagulant potency of the sulfated fucans but also the mechanism by which they exert this activity. Thus, the branched fucans from brown algae are direct inhibitors of thrombin, whereas the linear fucans from echinoderms require the presence of antithrombin or heparin cofactor II for inhibition of thrombin, as reported for mammalian glycosaminoglycans. The linear sulfated fucans from echinoderms have an anticoagulant action resembling that of mammalian dermatan sulfate and a modest action through antithrombin. A single difference of one sulfate ester per tetrasaccharide repeating unit modifies the anticoagulant activity of the polysaccharide markedly. Possibly the spatial arrangements of sulfate esters in the repeating tetrasaccharide unit of the echinoderm fucan mimics the site in dermatan sulfate with high affinity for heparin cofactor II.